School Management in Early Childhood Institutions (Docentes 2.0 Journal, 2023)
Currently, school management is a topic of great interest worldwide, especially in education, since it demands great attention to improving its processes.  Therefore, the objective of this research was to identify the main trends and challenges of school management in early-level educational institutions from a systematic review of the literature published in high-impact journals between 2018 and 2022. For its realization, the analytical method was used, under the positivist paradigm, with a quantitative approach of the descriptive type supported by meta-analysis and with an experimental design of cross-sectional order. The methodology used was content analysis supported by the guidelines of the PRISMA statement for the elaboration of reviews on a sample of 10 scientific articles published in journals indexed in different electronic databases. The results show the contextual variability and methodological weaknesses, which allowed us to systematize the contributions of the study. Finally, we highlight the achievements and shortcomings identified by the studies conducted so far on school management in initial-level educational institutions in the national context, as well as their coherence with the achievements of research at the international level. In conclusion, the review of the literature consulted reveals that, to date, there are not many articles that analyze the "educational management of the principal" as a variable of interest in early childhood educational institutions in Peru.
Keywords: Management; quality; initial education; model